Biodiversity of the Endophytic Fungi Isolated from Calotropis gigantea (L.) R.Br. - Isaivani Indrakumar, Muthumary Johnpaul, Srimathi Selvanathan, (Recent Research in Science and Technology, 2011)
Calotropis gigantea(L)R.Br., a widely used medicinal plant in India, were exploited for endophytes as a possible source of bioactive secondary metabolites. About 700 segments from 10 plants of Calotropis gigantea, collected from different locations of Guindy Campus, University of Madras during the year 2009–2010, were processed for the presence of endophytic fungi. A total of 13 fungal species viz., Aspergillus niger, Aspergillus flavipes, Alternaria porri, Curvularia lunata, Fusarium oxysporum, Nigrospora sphaerica, Colletotrichum falacatum, Pestalotiopsis sydowiana, Phoma exigua, Phomopsis archeri, Leptosphaerulina chartarum, and Mycelia sterilia, were isolated and identified based on the morphology of the fungal culture and characteristics of the spores.